Ruffeera Sock Industries Sdn. Bhd. / Razis Rahim, Noor Efanatrah Humumiri and Fatimah Zarah Liman - Rahim, Razis; Humumiri, Noor Efanatrah; Liman, Fatimah Zarah (Faculty of Applied Sciences, 2005)
Ruffeera Sock Industries Sdn. Bhd is the company that producing and selling school sock. This company is situated in Kawasan Perindustrian Shah Alam, Seksyen 16, Shah Alam Selangor. The company is owned by the Malay entrepreneur. There are a few factors selecting this business such as to produce sock with existing technology especially in textile industries. The company starts the business with required minimum capital. The company also abundant labors force with the right skill. The company had some future prospective for our business which is to increase a demand of the production as well as increase the sales and income level. As a result, these industries create healthy competitive environment among socks industries throughout Malaysia. In addition, it encourage Malay entrepreneur involve in business.